Tomato Quality Classification - Prathiba Pulagura; S. Muni Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The "Tomato Quality Classification" project aims to enhance the accuracy of tomato quality assessment using advanced machine learning techniques. Leveraging Convolutional Neural Networks like VGG-16 the project addresses the binary classification of tomatoes into two categories: Healthy and Rejected. Utilizing a dataset from Kaggle, which contains images of tomatoes, this project demonstrates the application of deep learning in agricultural quality control. By implementing VGG-16, the model effectively learns and distinguishes between healthy and rejected tomatoes, providing an automated solution for quality classification. The results exhibit high accuracy and efficiency, contributing significantly to quality assurance processes in the agricultural industry. This project not only improves quality control but also demonstrates the potential of AI in practical applications.